Meningkatkan Kinerja Keuangan UMKM melalui Sistem Informasi - Andik Prakasa Hadi; Rudjiono Rudjiono; Setiyo Adi Nugroho; Ahmad Zainudin; Agus Priyadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Digitalization in business has started to penetrate various sectors, particularly in assisting with the preparation of financial statements to improve financial performance. However, small and medium-sized enterprises (SMEs), as business entities in society, have not fully embraced digitalization. The main challenge is the lack of integration between SMEs' financial systems and technology, which impacts their financial performance. The current system cannot automatically record financial transactions, often lacks accuracy, contains errors, and is inefficient in recording and generating reports. To enhance the financial performance of SMEs by leveraging technology, a new information system has been designed to accelerate the preparation of automated financial statements, with a high level of accuracy in transaction recording. Three variabels were observed and tested, including automation, accuracy, and time efficiency. The system development followed the System Development Life Cycle (SDLC) methodology, while testing was conducted by analyzing questionnaire data. The test results revealed a strong relationship between the variabels. The information system significantly contributes to financial performance, accounting for 95%, and has a significant impact on financial performance. These findings indicate that the implementation of an accounting information system for financial management is highly feasible. Additionally, the system can serve as an effective technological solution to help improve the financial performance of SMEs.